Distribution of Trace Elements Controlled by Sector and Growth Zonings in Zircon from Feldspathic Pegmatites (Ilmen Mountains, the Southern Urals) - Ekaterina V. Levashova (Geosciences, 2021)
The present study contains the detailed ion microprobe data on trace and rare earth elements distribution in the large zircon crystal about 10×6 mm in size with distinct growth and sector zonings from Ilmen Mountains feldspathic pegmatite. The zircon crystal morphology is a combination of a prism {110} and a dipyramid {111}. It is found out that the growth sector of the prism {110} generally contains higher concentrations of Th, U, REE, Y, and Nb and exhibits a more gently sloping HREE distribution pattern and a steeper LREE distribution pattern, in contrast to zircon from the growth sector of the dipyramid {111} development. Such a sector zoning pattern was formed at a late stage in crystal growth, when the prism {110} began to prevail over the dipyramid {111}. The zircon studied displays the growth zoning formed of alternating bands in back-scattered electron (BSE) image: wide dark and thin light bands. The last ones contain elevated Th, U, REE, Y, Nb, and Ti concentrations, Th/U ratio and Се/Се*. This growth zoning is most probably due to simultaneous crystallization of other minerals that concentrate trace elements, e.g., apatite and monazite, and the lack of equilibrium between zircon and fluid (melt).